CALCULATION OF RELIABILITY OF TYPICAL COOLING SYSTEM BY DESIGNING OF TREE FAILURE METHOD - Pejović, B.; Vujadinović, D.; Perušić, M. (Journal of Engineering & Processing Management, 2010)
In the introductory part we give definitions and relationships to determine the reliability and probability of failure of technical systems. After that, the analysis and calculation of reliability, we proposed method, based on the construction of tree failure in the form of logical structure. The second part was performed to verify the model set on an example of typical cooling system. During this side of event for the loss has taken the minimum required flow of cooling fluid in heat exchanger . On the basis of tree failure in the general analysis is determined by the probability of adverse events, and reliability. At the end of the paper, the estimation of probability of failure, made the estimate, based on weight of i - event, using a typical circuit.